EQUIVALENCE AND ADEQUACY OF TRANSLATION OF SCIENTIFIC AND TECHNICAL TEXTS - Azimova , N.A.; Babamuradov , O.S. (Educational Research in Universal Sciences, 2023)
Scientific and technical translations, due to the special requirements for them, demand considerable attention to achieving the equivalence and adequacy of translation from English into Russian. In translation, there are a number of special methods aimed at creating an adequate translation. So, there are two methods of translation: direct translation and indirect translation. This article is devoted to considering means of achieving equivalence and adequacy in translation of texts of scientific and technical nature.